PENGARUH STUDENT TEAM ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR IPS DI KELAS III SEKOLAH DASAR - farida, Mustika; Marzuki, Marzuki; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the effect of learning the student team achievemen division model on social studies learning outcomes in grade III elementary schools. This study uses an experimental method in the form of Pre-Experimental Design type One Group Pretest-Posttest Design. The population is all students of class III SDN 14 South Pontianak consisting of 33 students, the sampling is non probability sampling type of convenience sampling that is all students of class III SDN 14 South Pontianak. The technique used in data collection is measurement with the data collection tool used is an objective written test. Based on the analysis of the data obtained the average pre-test results of students 57.33 and the average post-test results of students 77.03. After t test was obtained tcount of 14.38 with db = 33 -1 = 32 with a significant level (?) = 5% obtained ttable of 1.697, it turns out that tcount ? ttable or 14.38 ? 1.697 which means there is a significant influence on the application cooperative learning type student team achievement division. From the results of the calculation of effect size (ES), obtained ES of 0.68 with the criteria classified as moderate. This means cooperative learning type student team achievement division. give a positive influence on the acquisition of Social Sciences learning in class III SDN 14 South Pontianak. Keywords: Student Team Achievement Division, Learning Outcomes, Social Sciences.